Defining and measuring physicians' responses to clinical reminders - Vashitz,G; Meyer,J; Parmet,Y; Peleg,R; Goldfarb,D; Porath,A; Gilutz,H (J Biomed Inform, 2009)
Decision-support systems, and specifically rule-based clinical reminders, are becoming common in medical practice. Despite their potential to improve clinical outcomes, physicians do not always use information from these systems. Concepts from the cognitive engineering literature on users' responses to warning systems may help to define physicians' responses to reminders. Based on this literature, we suggest an exhaustive set of possible responses to clinical reminders, consisting of four responses named "Compliance", "Reliance", "Spillover" and "Reactance". We suggest statistical measures to estimate these responses and empirically demonstrate them on data from a large-scale clinical reminder system for secondary prevention of cardiovascular diseases. There was evidence for Compliance, probably since the physicians found the reminders informative, but not for Reliance, in line with the notion that Compliance and Reliance are two distinct types of trust in information from decision-support systems. Our research supports the notion that CDSS can promote closing the treatment gap and improve physicians' adherence to guidelines.